MANAJEMEN KEUANGAN KELUARGA MUSLIM DALAM KONDISI KETERBATASAN EKONOMI: ANALISIS HUKUM KELUARGA ISLAM - Umar Hassan Al Rasyid; Emha Hasan Aminullah (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study analyzes financial management practices among Muslim families under economic limitation and examines their relevance within Islamic family law. The study employs a descriptive qualitative approach through interviews and questionnaires with six Muslim family participants in Jember Regency. Unlike previous studies that tend to be normative and conceptual, this study examines empirical experiences of Muslim families at the micro level under significant economic constraint. The findings indicate that wives hold a dominant role as household financial managers, while husbands as breadwinners entrust daily needs to their wives. Participating families developed various economic adaptation strategies, including prioritizing essential needs, reducing expenditures, and reinforcing religious values such as qana'ah, patience, and tawakkal. Within Islamic family law, this practice does not contradict the principle of qiwāmah; rather, it represents domestic cooperation consistent with mu'āsyarah bil ma'rūf. Analysis was also conducted within the maqāṣid al-syarī'ah framework, particularly regarding preservation of life (ḥifẓ al-nafs) and lineage (ḥifẓ al-nasl). The husband's nafkah obligation is understood proportionally based on QS. at-Thalāq (65): 7, while the wife's role reflects fulfillment of domestic amanah. This study offers a concept of multidimensional Muslim family welfare built through domestic financial management, spousal trust, and internalization of religious values